Asymmetric Synthesis of 1-Aza-4-deoxypicropodophyllotoxin - Aigret, Benoit M.; Jacobs, Jeroen; Van Meervelt, Luc; De Borggraeve, Wim M. (Synlett, 2013)
In our search for new easily accessible analogues based on the natural product podophyllotoxin, we synthesized 1-aza-4-deoxypicropodophyllotoxin in good overall yield and excellent enantioselectivity. The synthesis was centered around a direct asymmetric Mannich reaction using d-proline as the key step for introduction of the chiral centres. Our synthesis of 1-aza-4-deoxypodophyllotoxin was hindered through the increased instability towards epimerization of the C2 position. We did, however, synthesized a new scaffold based on the opened lactone analogue.
Keywords: Mannich bases; asymmetric catalysis; amino aldehydes; enantioselectivity; total synthesis